Different interventions of physiotherapy in the improvement of planting sensitivity and balance of older people - Trennepohl, Cátia (2022)
Objective: to compare the effects of two different physical therapy protocols in the treatment of plantar sensitivity and balance in community-dwelling elderly women from de municipality of Panambi.Methods: pilot clinical trial, quantitative and descriptive. The participants answered a questionnaire about health conditions and self-perception of plantar sensitivity, after undergoing evaluation of plantar sensitivity with a Semmes-Weinstein esthesiometer. Only elderly women with reduced sensitivity were selected. Balance was assessed using the Berg Balance Scale and the Timed Up and Go test. The 13 selected participants were divided into a plantar sensitivity group and a proprioceptive group, with ten interventions performed with each group, with specific stimulus according to allocation in the groups. Afterwards, the participants were reassessed with an esthesiometer, Berg Balance Scale and Timed Up and Go. Comparisons of quantitative variables were performed using Student’s t test, with a significance level of 5% (p<0.05).Results: twelve elderly women concluded the study, but only five reported noticing a decrease in plantar sensitivity. The plantar regions with the greatest loss of sensitivity were in the metatarsals, lateral region of the foot and calcaneus. The medial region, on the other hand showed less sensory loss. After training, both groups showed a statistically significant improvement in plantar sensitivity. In balance, the plantar sensitivity group showed statistically significant results in the Timed Up and Go test and the proprioceptive group in the Berg Balance Scale.Conclusion: the training proved to be effective in the plantar sensitivity and balance of the participants, indicating that the combination of these interventions in the treatment of postural control is a good option for physical therapists.